2020
DOI: 10.1111/nyas.14445
|View full text |Cite
|
Sign up to set email alerts
|

Halogen exposure injury in the developing lung

Abstract: Owing to a high-volume industrial usage of the halogens chlorine (Cl 2) and bromine (Br 2), they are stored and transported in abundance, creating a risk for accidental or malicious release to human populations. Despite extensive efforts to understand the mechanisms of toxicity upon halogen exposure and to develop specific treatments that could be used to treat exposed individuals or large populations, until recently, there has been little to no effort to determine whether there are specific features and or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 99 publications
(240 reference statements)
0
4
0
Order By: Relevance
“…An immediate challenge in mass casualty scenarios is to develop strategies to protect survivors without prior knowledge of the inhaled toxicant. In addition, animal studies using pregnant dams and neonates have shown vulnerable subgroups are highly susceptible to pulmonary toxicants and may require population specific care (Addis, Molyvdas et al 2020, Addis, Aggarwal et al 2021.…”
Section: Challenges To Medical Countermeasures Developmentmentioning
confidence: 99%
“…An immediate challenge in mass casualty scenarios is to develop strategies to protect survivors without prior knowledge of the inhaled toxicant. In addition, animal studies using pregnant dams and neonates have shown vulnerable subgroups are highly susceptible to pulmonary toxicants and may require population specific care (Addis, Molyvdas et al 2020, Addis, Aggarwal et al 2021.…”
Section: Challenges To Medical Countermeasures Developmentmentioning
confidence: 99%
“…Almost half of the globally produced bromine is used to produce the latter, which can easily leach out, posing a persistent environmental problem [40,41]. As well as its environmental toxicity, bromine's storage and transportation equally pose hazards [42,43].…”
Section: Bromine and Bromination Agentsmentioning
confidence: 99%
“…Such environmental exposures may be compounded by chronic coexposure from unhealthy lifestyle practices, particularly smoking ( Morissette et al, 2014 ; Dai et al, 2021 ; Yang et al, 2021 ). On the other hand, highly toxic gases such as chlorine gas (Cl 2 ) ( Addis et al, 2020 ; Lazrak et al, 2020 ) have been misused as chemical threat agents and in chemical warfare because of their acute toxicity to respiratory system ( Govier and Coulson, 2018 ; Jacobs and Kovac, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled toxicants may variably induce lung pathophysiology causing toxicity/injury-associated acute conditions (such as pulmonary edema, acute respiratory distress syndrome) and/or chronic lung diseases such as asthma, chronic obstructive pulmonary disease (COPD), pulmonary fibrosis, among others ( Frank et al, 2016 ; Addis et al, 2020 ; Lazrak et al, 2020 ). Pathophysiological changes from acute and chronic toxic exposures are often characterized by inflammation, edema, fibrosis, and/or hyperplasia/dysplasia.…”
Section: Introductionmentioning
confidence: 99%